Estudio de rutas turísticas como un aporte a la economía de los habitantes del cantón Babahoyo - Peralta Gutiérrez, Vanessa Rosalba (2018)
The following research work was carried out in the city of Babahoyo Province of Los Ríos, known for its natural and cultural attractions being the most outstanding Casa de Olmedo, Balsa Blanca, the Cathedral, Cerro Cachari, Malecón, among others, oriented to the Study of Tourist Routes for a contribution to the economy of the inhabitants of the Babahoyo canton allowing them to enjoy their tourist places. In spite of existing well-known tourist sites, they are few visited by the tourist due to the scarce tourist routes that prevents the economic development of the corner. We can determine that the implementation of a tourist route in Babahoyo canton is of great interest since it will allow the development of entrepreneurial activities generating economic stability for its inhabitants, as well as tourists will be able to enjoy cozy places that satisfy their basic needs.